Activity of heterotrophic bacteria from marine area of Siak District against pathogenic bacteria. (December 2018) - Nursyirwani, N; Feliatra, F; Yoswaty, D; Dinata, R L
Abstract: The objective of this research was to isolate and to characterize heterotrophic bacteria in the marine area of Siak District of Riau Province based on sequence 16S rRNA and to examine the antagonism activity against pathogenic bacteria ( Vibrio sp., Aeromonas sp. and Pseudomonas sp.). Water samples were collected from two sea waters sites: waters with salinity of 15 ppt (station 1) and that at salinity of 27 ppt (station 2). Total heterotroph count in station 1 (7.04 × 10 7 cfu/mL) was higher than that in station 2 (6.04 × 10 7 cfu/mL). Antagonism test indicated that nine isolates (RM3, RM4, RM5, RM6, RM8, RM11, RL15, RL17 and RL 24) had potency in inhibiting the growth of tested pathogens.